Microneedling with topical 5-fluorouracil in the localized stable vitiligo - Is this the way out? - Our experience: A hospital-based study - Ankit K Singrodia; Rajesh Datt Mehta; Divya Sharma; Paras Choudhary; Bhikamchand Chand Ghiya; Jyothi Bai S (Wolters Kluwer Medknow Publications, 2021)
Background: Vitiligo is a dermatological challenge with a major socio-psychological concern. Despite the availability of numerous medical and surgical treatment options, a single universally reliable therapeutic modality is yet to emerge due to the variability of response rate in different patients. Purpose: The objective of this study was to assess the safety and efficacy of microneedling along with topical 5-fluorouracil (5-FU) solution application in localized stable vitiligo. Methods: This open, nonrandomized, single-arm study was enrolled with 100 patients with localized stable vitiligo. Microneedling with topical 5-FU solution application was performed on 204 patches. The procedure was performed fortnightly for maximum 6 months. Results: At the end of 3 months, good to excellent (Grade IV) repigmentation was noted in 106 patches (51.96%) and Grade I to Grade II repigmentation was seen in 56 (27.45%) patches whereas at the end of follow-up, 128 (62.74%) patches showed good to excellent response. Conclusion: In conclusion, the results of this study showed that needling with 5-FU is a simple, cost-effective, and well-tolerated procedure which can be used as an alternative or additive modality in the treatment of localized stable vitiligo.